BIOFEEDBACK IN THE MAGNETIC FIELD (ON STEREOTOPOGRAPHY OF COGNITIVE FUNCTIONS) - K. G. Mazhirina; M. A. Pokrovskiy; M. V. Rezakova; A. A. Savelov; A. A. Sokolov; Ye. D. Petrovskiy; Ye. A. Levshakova; Yu. A. Ganenko; M. B. Shtark (Бюллетень сибирской медицины, 2013)
The brain was mapped on-line using fMRI technology in the process of the development of self-regulation skills. We studied the dynamics of new neural networks being created in the real and simulated biofeedback models. It was shown that immersion in a virtual story brings about the large involvement of cortical areas, which are characterized by high values of voxels in the middle-temporal, occipital and frontal regions. We discuss the qualitative characteristics of the real and the imitation game periods.